دراسة راجعة على لاكتات ديهدروجيناز (LDH) المصل عند مرضى فقر الدم العرطل الخلايا - حسين فراس (Latakia University Journal -Medical Sciences Series, 2019)
Megaloblastic anemia is characterized by decreased hemoglobin level with elevated Mean Corpuscular Volume (MCV). Deficiency of vitamins -B12 and/ or Folic acid leads to impaired DNA synthesis leading to ineffective erythropoiesis and intramedullary hemolysis in patients of megaloblastic anemia. This leads to increased unconjugated bilirubin, serum LDH (Lactate Dehydrogenase) and some degree of cytopenia. Aims of study: To study the level of serum LDH in megaloblastic anemia patients, and study the Correlation between serum LDH and serum hemoglobin concentration. Material and methods: This is a retrospective study. The study was conducted on patients admitted in Service of Hematology, Tishreen University hospital, during the period of 1 January 2017 to 30 December 2017. The medical records of 52 cases of Megaloblastic anemia were selected for study. Patients diagnosed as megaloblastic anemia with Hb ≤ 12 g/dl& MCV ≥ 100 fl whose serum LDH level and CBC was measure were selected for the study Conclusion: In this study, serum LDH level was significantly elevated in patients of megaloblastic anemia. Total serum LDH levels which is more than 5 times-7 times the upper limit of normal are diagnostic of megaloblastic anemia without the necessity of bone marrow aspiration in patients of a regenerative macrocytic anemia with MCV which is more than 110 fl . present study had also shown that there was an inverse relationship between serum LDH and serum hemoglobin In Megaloblastic anemia. يعرف فقر الدم العرطل الخلايا (Megaloblastic anemia) بانخفاض تركيز الهيموغلوبين مع زيادة بحجم الكريات الحمراء حيث يكون حجم الكرية الوسطي (MCV) أكبر من 100 فمتولتر. ان عوز B12 وحمض الفوليك يؤدي الى نقص تشكل DNA وبذلك تكون الكريات الحمراء اللافعال والانحلال داخل النقي عند مرضى فقر الدم العرطل الخلايا. الامر الذي يؤدي الى ارتفاع البيلروبين غير المباشر، ارتفاع انزيم LDH ودرجة من قلة الكريات الشاملة. هدف الدراسة: دراسة اهمية ارتفاع LDH المصل عند مرضى فقر الدم العرطل الخلايا، ودراسة العلاقة بين تركيز LDH المصل وتركيز خضاب المصل بالإضافة الى تحديد قيمة عتبوية ل LDH المصل تعتبر مشخصة لفقر الدم العرطل الخلايا دون اللجوء الى الإجراءات الباضعة كفحص نقي العظم. المواد والطرائق: دراسة راجعة على 52 مريض مشخص لديهم فقر دم عرطل الخلايا اعتمادا على الدراسة الخلوية لنقي العظم قبلوا للدراسة في شعبة امراض الدم– مشفى تشرين الجامعي باللاذقية خلال العام 2017. كانت معايير الاشتمال بالدراسة المرضى البالغين أكبر من 14 سنة والذين شخص لديهم فقر دم عرطل الخلايا (خضاب اقل من 12 غ/دل مع MCV أكبر من 100 فمتولتر). اجري لجميع المرضى تعداد دم كلي، LDH المصل ,شبكيات المصل ودراسة نقي العظم اثناء القبول للدراسة. النتائج: كانت LDH المصل مرتفعة بشدة عند مرضى فقر الدم عرطل الخلايا وبذلك فهي تلعب دورا أساسيا في التشخيص حيث ان ارتفاع LDH المصل أكثر من خمسة الى سبعة اضعاف الطبيعي تعتبر مشخصة لفقر الدم العرطل الخلايا دون الحاجة الى اجراء الدراسة الخلوية على نقي العظم عند مريض فقر دم كبير الكريات غير متجدد مع MCV أكبر من 110 فمتولتر. كما أظهرت هذه الدراسة وجود علاقة ارتباط عكسية بين قيمة LDH المصل وتركيز الهيموغلوبين عند مرضى فقر الدم العرطل الخلايا.